2020
DOI: 10.3390/s20051493
|View full text |Cite
|
Sign up to set email alerts
|

Motion Artifact Reduction in Wearable Photoplethysmography Based on Multi-Channel Sensors with Multiple Wavelengths

Abstract: Photoplethysmography (PPG) is an easy and convenient method by which to measure heart rate (HR). However, PPG signals that optically measure volumetric changes in blood are not robust to motion artifacts. In this paper, we develop a PPG measuring system based on multi-channel sensors with multiple wavelengths and propose a motion artifact reduction algorithm using independent component analysis (ICA). We also propose a truncated singular value decomposition for 12-channel PPG signals, which contain direction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 25 publications
0
57
0
1
Order By: Relevance
“…The result showed a reduction of error in active state HR estimation [123]. Fitbit's PurePulse 2.0 introduces a PPG sensor with multi-wavelength LEDs, which should provide better accuracy and robustness compared to their previous generation PurePulse R , equipped with only green LEDs [123], [124]. The accuracy validation of these newly debut PPG technologies is expected to stimulate the interest for further research.…”
Section: Discussion On Smartwatch Candidates For Mental Health Monmentioning
confidence: 93%
See 2 more Smart Citations
“…The result showed a reduction of error in active state HR estimation [123]. Fitbit's PurePulse 2.0 introduces a PPG sensor with multi-wavelength LEDs, which should provide better accuracy and robustness compared to their previous generation PurePulse R , equipped with only green LEDs [123], [124]. The accuracy validation of these newly debut PPG technologies is expected to stimulate the interest for further research.…”
Section: Discussion On Smartwatch Candidates For Mental Health Monmentioning
confidence: 93%
“…A study has demonstrated the use of a similar LED configuration as Apple Watch Series 6 (4 cluster LEDs (green, red, and infrared)). The result showed a reduction of error in active state HR estimation [123]. Fitbit's PurePulse 2.0 introduces a PPG sensor with multi-wavelength LEDs, which should provide better accuracy and robustness compared to their previous generation PurePulse R , equipped with only green LEDs [123], [124].…”
Section: Discussion On Smartwatch Candidates For Mental Health Monmentioning
confidence: 95%
See 1 more Smart Citation
“…The location freedom of PPG allows designs that can be worn as a ring or bracelet to minimize the motion artefacts; however, due to the usage of rigid components, consumer wearables are shown to be only accurate only in limited conditions such as resting and slow walking. [ 29 ] Therefore, PPG measurements of wafer‐based wearables still require post processing by software algorithms to eliminate present motion artifacts. Algorithm based approaches generally offers case specific solutions that remain insufficient for realistic cases including randomly interfered multiple noise sources.…”
Section: Ppg and Optoelectronic Wearablesmentioning
confidence: 99%
“…Zhang et al suggest the motion artifact reduction algorithm using green PPG signal and IR PPG signal using wavelet transform and signal reconstruction. Lee et al suggest combining 12 channel PPG signals generated by four PPG sensors each containing red, green and infrared LEDs [26].…”
Section: Related Workmentioning
confidence: 99%